Islamic Education in Schools and Madrasas: Research Trend and Issues Based on Bibliometric Evidence - Edi Nurhidin; Maimunatun Habibah; Mohd Roslan Mohd Nor (Nadwa: Jurnal Pendidikan Islam, 2025)
Islamic education studies are currently undergoing significant advancements in global publications. This study explores the progress in Islamic education publications across schools and madrasas through a bibliometric analysis. A keyword search in the Scopus database yielded 403 relevant publications from 2004 to 2023. Using the Bibliometrix R package, Biblioshiny, VOSviewer, and Microsoft Excel, we observed significant growth in this field. The journal "Religion" emerged as the most prominent source, while the most cited document was authored by Denessen et al. The leading contributor is Tamuri, A.H., and the University Kebangsaan Malaysia stands out as the most productive institution. Notably, Indonesia is recognized as the top publishing country, reflecting a high level of international collaboration. Current trending topics include tolerance, social media, religious moderation, leadership, and Islamic education management. These findings underscore the increasing significance of Islamic education research, particularly highlighting the contributions of Indonesian scholars and institutions and emphasizing the importance of regional perspectives and international cooperation. However, this study is constrained by its reliance on the Scopus database and English-language publications. Overall, this bibliometric analysis presents a systematic overview of trends and developments in Islamic education research, offering valuable insights for scholars and policymakers.